Royal jelly: A boon of nature - Jha, Sudeepa Kumari; Monobrullah, Md; Kumar, Anjani; Chakravarty, Milan Kumar (Indian Farming, 2023)
Royal jelly is a bee product secreted by worker bees. It is responsible for morphological characteristics of queen bee. It is a rich source of protein and has high medicinal importance. It is also used in food industries as dietary supplement and in cosmetic industries. But, it is not considered as a bee product in traditional bee keeping because after secretion, it is immediately consumed by bees and is not stored. Harvesting of royal jelly becomes feasible only in the case of queen rearing. The most common method of mass rearing of queen bee is grafting of larvae in artificial queen cup. The royal jelly is extracted with aspirator or water vacuum pump and is stored in jar after filtering with nylon net. The shelf life of fresh royal jelly is very small. A small beekeeper may also harvest royal jelly along with honey.